(untitled) (Communications in Mathematical Research, 2021)
Let f : I → I be a continuous map. If P(n, f) = {x ∈ I; f^n (x) = x } is a finite set for each n ∈ N, then there exists an anticentered map topologically conjugate to f, which partially answers a question of Kolyada and Snoha. Specially, there exists an anticentered map topologically conjugate to the standard tent map.